THE LEARNING ACHIEVEMENT OF PASCH ALUMNI AND REGULAR STUDENTS RELATED TO ACCELERATION PROGRAM IN GERMAN DEPARTMENT - Adisty Frisca Tarisca; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2017)
Abstract: This research is conducted by the purpose to describe the effectiveness of the acceleration program in German Department of State University of Malang, the perception and also the projection of acceleration program students about the program. This study uses correlational-quantitative research method. The research instruments used are in the form of documentation of student learning result and questionnaire sheets. The analysis conducted i.e. normality test, homogeneity variance test, independent t-test and Mann Whitney test. Furthermore, interpretation and discussion of data is being established. Based on the results of the data analysis, it is concluded that the acceleration program runs effectively. The learning achievement of students from acceleration program appears higher compared with students from non-acceleration program. However, even an effective programs do not escape the shortcomings and advantages. Based on the results of the questionnaire filled by students from acceleration program (the questionnaire in this case is not the main focus of hypothesis testing), it is known that acceleration students are very enthusiastic and convinced that they will graduate soon by this program. However, during the process of the program, found that the confidence of respondents began to decrease and afterwards emerging problems that felt inhibit them. Keywords: learning achievement, acceleration program, PASCH, German department, German language